Antaseden Dari Word Of Mouth Pada Kedai Kopi Lokal Di Indonesia - I Wayan Astu Upekca; Willy Dery Adrian; Yudha Syafendra; Arnolt Kristian Pakpahan (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
This Article examines the”effect”of store atmosphere”& price”fairness to word of mouth that is mediated by customer satisfaction.”The sample being”use in this study are”210 respondents who have bought and visited coffee shops at least 2 times in the last one year. The”survey”was”conducted“by”filling”out”an”online”questionnaire with google form. The”testing”is”conducted by”Structural”Equation”Model (SEM).”The”findings”of this”study are : (1) store atmosphere”has a positive..effect on customer..satisfaction, (2) price fairness has”a positive”effect on customer”satisfaction, (3) customer satisfaction has a”positive effect”on customer loyalty, (4) customer satisfaction has a positive effect on word of mouth, (5) customer loyalty has a positive effect on word”of mouth, and (6) customer satisfaction”has a”positive effect on word”of mouth mediated by customer”loyalty.